USE OF GUIDED ENDODONTICS IN TREATING TEETH WITH PULP OBLITERATION DUE TO CALCIFICATION AND THE RELEVANCE OF CLINICAL SCRUTINY IN DECISION MAKING: A CLINICAL CASE REPORT - Damasceno, Ingrid Barros da Costa; Magalhães, João Pedro de Mello Dutra; Belo Júnior, Paulo Henrique dos Santos; Campos, Adriano Rocha; Pinho, Marco André de Berrêdo; Amaral, Georgiana; Senna, Plinio Mendes; Perez, Cesar dos Reis (ARACÊ, 2025)
Endodontic treatment of teeth with pulp canal obliteration (PCO) represents a procedure of higher complexity, as it requires the professional to have precise control over access direction, considering that essential references are lost. This difficulty becomes even more critical when the PCO extends to the apical third of the tooth. In such cases, a relatively recent alternative emerges as a viable option that facilitates and provides greater control over the procedure: guided endodontics. In this process, surgical guides are designed using scans of the arch and high-resolution tomography scans and then printed to integrate perfectly with high-precision sleeve and drill systems. This allows pulp obliteration to be bypassed up to the portion of the canal with preserved anatomy. However, this procedure cannot be performed without a specialist's parallel supervision, as minor trajectory deviations can result in root perforations. This clinical case report illustrates a scenario in which the guided procedure was interrupted by the specialist's decision. Upon evaluating the depth already cleared and the image of the obstruction, the specialist considered the possibility of a deviation in the trajectory, although this was not observed radiographically. Therefore, he requested a new high-resolution tomography, which confirmed the deviation of the trajectory from the palatine, although it remained parallel to the root canal. Thus, the professional opted for a traditional approach, aided by the operating microscope, and achieved a successful treatment. In conclusion, a situation is demonstrated that, although not frequently reported, shows the vital importance of carefully monitoring the entire clinical step-by-step by the specialist.